2014
DOI: 10.1007/s11524-014-9905-4
|View full text |Cite
|
Sign up to set email alerts
|

Emergency Department Use among HIV-Infected Released Jail Detainees

Abstract: Release from short-term jail detention is highly destabilizing, associated with relapse to substance use, recidivism, and disrupted health care continuity. Little is known about emergency department (ED) use, potentially a surrogate for medical, psychiatric, or social instability, by people living with HIV/AIDS (PLWHA) leaving jails. All ED visits were reviewed from medical records for a cohort of 109 PLHWA in the year following release from county jail in Connecticut, between January 1, 2008 and December 31, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
12
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 74 publications
5
12
0
Order By: Relevance
“…Several studies found that compared to use by the general population, ambulatory care use was higher in prison [ 10 ], and emergency department use and hospitalization were higher post-release [ 5 , 22 , 23 ]. However, most studies conducted to date have limitations that challenge their internal and external validity, including small or select samples [ 5 , 19 21 , 24 ], the lack of general population comparator groups [ 11 , 12 , 14 , 15 , 17 21 , 24 , 25 ], the use of self-reported data [ 15 , 17 20 , 25 ], and the use of data from over 20 years ago [ 11 , 13 ]. Further, no studies have examined health care utilization both in prison and on release.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies found that compared to use by the general population, ambulatory care use was higher in prison [ 10 ], and emergency department use and hospitalization were higher post-release [ 5 , 22 , 23 ]. However, most studies conducted to date have limitations that challenge their internal and external validity, including small or select samples [ 5 , 19 21 , 24 ], the lack of general population comparator groups [ 11 , 12 , 14 , 15 , 17 21 , 24 , 25 ], the use of self-reported data [ 15 , 17 20 , 25 ], and the use of data from over 20 years ago [ 11 , 13 ]. Further, no studies have examined health care utilization both in prison and on release.…”
Section: Introductionmentioning
confidence: 99%
“…This relatively short term stay and rapid release from jail, compared to more stable prison populations, is a significant public health challenge for individuals and communities. Incarceration makes individuals more likely to relapse to substance abuse, and non-adherence to mental and physical health treatment programs [ 17 , 18 , 19 ]. Jail residents may also become an important vector for communicable disease being cycled in and out of jail populations.…”
Section: Introductionmentioning
confidence: 99%
“… 10 Despite these challenges, studies that followed cohorts in the first year postrelease found high proportions of ED use, ranging from 25% to 56% after release from prison, 11 12 and 65% of individuals with HIV after release from jail. 13 National studies found individuals with past-year criminal justice involvement were more likely than the overall population to have used the ED or been hospitalised in the last year. 14 15 Other studies linked administrative data from correctional departments, hospitals and Medicare claims to show higher rates of ED visits and hospitalisations among those released from correctional institutions, particularly for mental health, substance use disorders and other ambulatory care sensitive conditions.…”
Section: Introductionmentioning
confidence: 99%